Frequent detection of high human papillomavirus DNA loads in oral potentially malignant disorders. (January 2016) - Pierangeli, A.; Cannella, F.; Scagnolari, C.; Gentile, M.; Sciandra, I.; Antonelli, G.; Ciolfi, C.; Russo, C.; Palaia, G.; Romeo, U.; Polimeni, A.
Abstract: Human papillomavirus (HPV) is estimated to be the cause of 40–-80% of the squamous cell carcinoma of the oropharynx but only of a small fraction of the oral cavity cancers. The prevalence of oral HPV infection has significantly increased in the last decade, raising concerns about the role of HPV in progression of oral potentially malignant disorders (OPMD) toward squamous cell carcinomas. We sought to study HPV infection in patients with oral lesions, and in control individuals, using non-invasive and site-specific oral brushing and sensitive molecular methods. HPV DNA positivity and viral loads were evaluated in relation to patient data and clinical diagnosis. We enrolled 116 individuals attending Dental Clinics: 62 patients with benign oral lesions (e.g. fibromas, papillomatosis, ulcers) or OPMD (e.g. lichen, leukoplakia) and 54 controls. Oral cells were collected with Cytobrush and HPV-DNA was detected with quantitative real-time PCR for the more common high-risk (HR) and low-risk (LR) genotypes. HPV detection rate, percentage of HR HPVs and HPV-DNA loads (namely HPV16 and in particular, HPV18) were significantly higher in patients than in controls. Lichen planus cases had the highest HPV-positive rate (75.0%), hairy leukoplakia the lowest (33.3%). This study detected unexpectedly high rates of HPV infection in cells of the oral mucosa. The elevated HR HPV loads found in OPMD suggest the effectiveness of quantitative PCR in testing oral lesions. Prospective studies are needed to establish whether elevated viral loads represent a clinically useful marker of the risk of malignant progression.